Trends and research frontiers in organizational commitment and job performance - Rumangkit, Stefanus (PHINISI, 2025)
This study aims to map the latest research related to organisational commitment and job performance. Another objective is to identify factors that can be studied regarding organisational commitment and job performance. The research method used is the bibliometric method with secondary data sources. The data analysed are articles found in the Scopus database. The keywords used to search for data are ‘organizational commitment’ and ‘job performance’ published between 2020 and 2025. The selected articles are within the scope of business, management, and accounting research. Bibliometric analysis identified six main groups of factors related to organizational commitment and job performance. Five factors with great potential for future research are emotional intelligence, employee performance, organizational identification, the public sector, and civil servants. These factors indicate areas that need more attention in the context of organizational commitment and job performance.